2012
DOI: 10.1021/jp209636a
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Multiple Photon Dissociation Spectroscopy of Cationized Histidine: Effects of Metal Cation Size on Gas-Phase Conformation

Abstract: The gas phase structures of cationized histidine (His), including complexes with Li(+), Na(+), K(+), Rb(+), and Cs(+), are examined by infrared multiple photon dissociation (IRMPD) action spectroscopy utilizing light generated by a free electron laser, in conjunction with quantum chemical calculations. To identify the structures present in the experimental studies, measured IRMPD spectra are compared to spectra calculated at B3LYP/6-311+G(d,p) (Li(+), Na(+), and K(+) complexes) and B3LYP/HW*/6-311+G(d,p) (Rb(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 55 publications
5
67
0
Order By: Relevance
“…Zero point energy (ZPE) corrections scaled by 0.989 were determined in order to provide 0 K relative energies and thermal corrections to free energies at 298 K. For comparison to IRMPD experimental spectra, calculated frequencies were scaled by 0.975, as this factor leads to good agreement between calculated and experimentally well-resolved peaks and is consistent with previous IRMPD studies of metal-amino acid complexes. 13,[30][31][32][33][34] Calculated vibrational frequencies are broadened using a 15 cm À1 full width at half maximum Gaussian line shape for comparison with experimental spectra.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Zero point energy (ZPE) corrections scaled by 0.989 were determined in order to provide 0 K relative energies and thermal corrections to free energies at 298 K. For comparison to IRMPD experimental spectra, calculated frequencies were scaled by 0.975, as this factor leads to good agreement between calculated and experimentally well-resolved peaks and is consistent with previous IRMPD studies of metal-amino acid complexes. 13,[30][31][32][33][34] Calculated vibrational frequencies are broadened using a 15 cm À1 full width at half maximum Gaussian line shape for comparison with experimental spectra.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Compared with their CID spectra (generated on a Finnigan-LTQ-FT mass spectrometry (Thermo, Bremen, Germany), which has a low-mass cutoff of 50 Th), ours show more fragment ions, including the loss of neutral Trp giving the M + cation in high abundance for all the metals (Table 1 and Supporting Information, Figure S3). + upon IR photodissociation [35]. In an earlier publication, we reported detailed fragmentation reactions of protonated aromatic AAs [43].…”
Section: Resultsmentioning
confidence: 97%
“…The precursor ion scans (Tables S1, Supporting Information) show that this ion may be formed by one of two routes, through the initial loss of either NH 3 however, no mechanism was reported [35]. Reaction pathways showing the losses of NH 3 and CO 2 in different sequential orders are outlined in Scheme 1 (pathways 2 and 3).…”
Section: Loss Of (Nh 3 + Co 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that all available carbonyl oxygens are sodium binding sites in the most stable structures of sodium‐cationized peptides . As a result, the conformation of a sodiated peptide ion will be different from its protonated counterpart in which a proton often associates with one or two basic sites.…”
Section: Resultsmentioning
confidence: 99%